Efek latihan peregangan pada fleksibilitas bagi siswa - Hidayatullah, Muhammad A'raaf; Doewes, Muchsin; Kunta Purnama, Sapta (Universitas Nusantara PGRI Kediri, 2022)
Flexibility is an important basic component in sports activities, which supports the achievement of the maximum performance of an athlete. Exercises are needed for stretching proper this study aimed to determine: (1) the effect of passive static stretching on shoulder flexibility, (2) the effect of Proprioceptive Neuromuscular Facilitation (PNF) stretching on shoulder flexibility (3) determine which exercise is better on shoulder flexibility between stretching and PNF. the method used is experimental with pretest and post-test design. The research sample was 16 students of the Sport Coaching Education study program, Faculty of Sport, Sebelas Maret University, Surakarta. research data was obtained using the sit and reach test. Data analysis using an independent sample test with the help of the SPSS 22.0 program. The results of the study (1) passive static stretching effect on togok flexibility, the test results show the value of sig. 0.00 < 0.05. (2) practice PNF affects the flexibility of stakes. The study results show that both passive tactical stretching exercises and PNF exercises have a significant effect on increasing flexibility, but empirical data states that PNF exercise is more effective in increasing flexibility.